Legal Protection against BRI's Quick Response Code Indonesian Standard (QRIS) Transactions in Micro, Small, and Medium Enterprises in Kartasura District - Wida Daning Mulia; Moh. Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2025)
Quick Response Code Indonesian Standard (QRIS) is a digital payment system implemented by Bank Indonesia to unite various QR Code-based payment service providers in one national standard. This research aims to find out: 1) QRIS transaction regulations in Indonesia, and 2) Legal protection of Bank Rakyat Indonesia (BRI) QRIS transactions in Micro, Small, and Medium Enterprises (MSMEs) in Kartasura District. This research uses a normative juridical approach with a case study conducted to obtain an overview of how the regulation is applied in practice, especially in the use of BRI QRIS by Micro, Small and Medium Enterprises in Kartasura. The results showed that the regulation of QRIS transactions in Indonesia has a strong legal basis, especially with the existence of Bank Indonesia Regulation (PBI) No. 22/20/PBI/2020 concerning Payment Service Providers, Electronic Information and Transactions Law (ITE Law), and Consumer Protection Law. BRI QRIS transactions in Kartasura Micro, Small and Medium Enterprises are quite helpful for business actors in making faster and more efficient transactions. However, there are still some problems that are often faced, such as potential fraud through QR Code forgery, system disruptions, and limited access to dispute resolution mechanisms. Therefore, synergy is needed between regulators, banks, and Micro, Small and Medium Enterprises to ensure that the implementation of QRIS can run optimally, safely, and provide maximum benefits for all parties involved.